The importance of the European funds for the development and competitiveness of the Wrocław Agglomeration - Jolanta Malec (Economic and Environmental Studies (E&ES), 2019)
This article presents an attempt to determine the importance of the European funds for the development and competitiveness of the Wrocław Agglomeration. The first part of this study presents the definitions used in this article and the characteristics of the Wrocław Agglomeration. The next part sets out the most important projects implemented with the use of the European Union funds in the Wrocław Agglomeration and shows the effects of using these funds in the region. Some of the projects implemented in the Wrocław Agglomeration were presented under the 2014-2020 financial scheme. In the final part of the study, an attempt is made to determine the importance of using funds for the development of the competitiveness of the Wrocław Agglomeration.
Keywords: O20; P45; R11; 330; the European funds; competitiveness; the Wrocław agglomeration